PENGARUH IKLIM ORGANISASI DAN SIKAP KERJA TERHADAP KINERJA KARYAWAN PT BESTAMA LOGISTICS INDONESIA - Johanes, Vincen; Nainggolan, Nora Pitri (LPPM Universitas Putera Batam, 2021)
The research objective was to determine the effect of organizational climate and work attitudes partially and simultaneously on the performance of employees of PT Bestama Logistics Indonesia. The number of samples was 103 people and the respondents were the employees of PT Bestama Logistics Indonesia. The method used is quantitative causality with multiple linear regression analysis. The results showed that the organization’s climate had a significant effect of 4.451, greater than the t table of 1.98326 and significant with the sig t value of 0.000, less than 0.05. While work attitude has a significant effect of 2.524 greater than t table 1.98326 and significant with a sig t value of 0.013 less than 0.05. Then simultaneously the organization’s climate and work attitude have a significant effect of 0.000 <0.05 and the F value of 14.107> F table 3.09 on the performance of employees at PT Bestama Logistics Indonesia. The conclusion of the organization’s climate has a partial significance effect, then work attitude has partial significance and simultaneously the organization’s climate and work attitude have a significant effect on the performance of employees of PT Bestama Logistics Indonesia.